Dehydration-induced responses of primary photosynthetic processes and spectral reflectance indices in Antarctic Nostoc commune - Barták Miloš; Hazdrová Jana; Skácelová Kateřina; Hájek Josef (Czech Polar Reports, 2016)
In this study, we investigated the relationship between relative water content (RWC) of N. commune colonies recorded during gradual dehydration and (i) normalized difference vegetation index (NDVI), (ii) photochemical reflectance index (PRI), and (iii) primary photochemical processes of photosynthesis, effective quantum yield of photosynthetic processes (PhiPSII) in photosystem II particular. PRI increased from -0.05 to 0.02 with RWC decrease from 100% (full hydration) to 0% (dry state). NDVI showed somewhat curvilinear relationship with desiccation with minimum value of 0.25 found at 10% RWC. Negative effect of suprasaturation of N. commune colony with water on effective quantum yield (PhiPSII) was found at RWC range 80-100%. At the RWC range, PhiPSII reached only 50 % of maximum found at RWC of 30%. In general, desiccation-response curve of showed polyphasic character with three main phases (phase I – constant PhiPSII values, phase II – an increase with desiccation at RWC 80-30%, and phase III – sigmoidal decrease with desiccation at RWC 0-30%). Práce je zaměřena na analýzu spektrálních indexů PRI a NDVI, v souvislosti s dehydrací kolonie sinice Nostoc commune. Souběžně s indexy spektrální reflektance byly měřeny a analyzovávy fotosyntetické parametry fluorescence chlorofylu, zejména efektivní kvantový výtěžek fotosyntetických procesů ve fotosystému II (PS II) In this study, we investigated the relationship between relative water content (RWC) of N. commune colonies recorded during gradual dehydration and (i) normalized difference vegetation index (NDVI), (ii) photochemical reflectance index (PRI), and (iii) primary photochemical processes of photosynthesis, effective quantum yield of photosynthetic processes (PhiPSII) in photosystem II particular. PRI increased from -0.05 to 0.02 with RWC decrease from 100% (full hydration) to 0% (dry state). NDVI showed somewhat curvilinear relationship with desiccation with minimum value of 0.25 found at 10% RWC. Negative effect of suprasaturation of N. commune colony ...